Mirroring the dialectic of inclusion and exclusion in ethnoheterogenesis processes - Tiesler, Nina Clara (2018)
Regarding inclusion and exclusion processes, the study of ethnic relations has been a common pursuit in Sociology and Anthropology, both in the past and in the present, especially – though not exclusively – in historical contexts marked by heightened migration. While the work of many sociologists and socialcultural anthropologists can be applied directly to social policy and welfare, this contribution is an attempt at refining the theoretical understanding of social and cultural processes through merging perspectives from both disciplines. It does so by choosing a subject matter which ranges from the micro level of individual agency and interaction to the macro level of systems and the social structure: the coming-into-being of ethnicities in the light of societal and cultural change, and as a social form of symbolic collectivity that may enhance as much as restrict individuality.